sMAdCAM: IL-6 Ratio Influences Disease Progression and Anti-Viral Responses in SARS-CoV-2 Infection - Jagtap, Dhanashree; Bhor, Vikrant M.; Bhowmick, Shilpa; Kasarpalkar, Nandini; Sagvekar, Pooja; Kulkarni, Bhalchandra; Pathak, Manish; Chatterjee, Nirjhar; Dolas, Pranam; Palav, Harsha; Kaginkar, Snehal; Bhagat, Sharad; et al. (Frontiers in Immunology, 2021)
The role of sMAdCAM, an important gut immune migratory marker, remains unexplored in COVID-19 pathogenesis considering recent studies positing the gut as a sanctuary site for SARS-CoV-2 persistence. Thus, assimilating profiles of systemic inflammatory mediators with sMAdCAM levels may provide insights into the progression of COVID-19 disease. Also, the role of these markers in governing virus specific immunity following infection remains largely unexplored. A cohort (n=84) of SARS-C0V-2 infected individuals included a group of in-patients (n=60) at various stages of disease progression together with convalescent individuals (n=24) recruited between April and June 2020 from Mumbai, India. Follow-up of 35 in-patients at day 7 post diagnosis was carried out. Th1/Th2/Th17 cytokines along with soluble MAdCAM (sMAdCAM) levels in plasma were measured. Also, anti-viral humoral response as measured by rapid antibody test (IgG, IgM), Chemiluminescent Immunoassay (IgG) and antibodies binding to SARS-CoV-2 proteins were measured by Surface Plasmon Resonance (SPR) from plasma.IL-6 and sMAdCAM levels among in-patients inversely correlated with one another. When expressed as a novel integrated marker –sMIL index (sMAdCAM/IL-6 ratio), these levels were incrementally and significantly higher in various disease states with convalescents exhibiting the highest values. Importantly, sMAdCAM levels as well as sMIL index (fold change) correlated with peak association response units of receptor binding domain and fold change in binding to spike respectively as measured by SPR. Our results highlight key systemic and gut homing parameters that need to be monitored and investigated further to optimally guide therapeutic and prophylactic interventions for COVID-19.